Considerations for athletes with eating disorders based on levels of care - Flatt, R. E.; Miller, A. J.; Foreman, T.; Shannon, J. (Current Sports Medicine Reports, 2022)
This article provides an overview of levels of care for eating disorders (EDs) and considerations that are specific to elite athletes. We discuss the following levels of care in terms of ED pathology and treatment aspects that may be unique to athletes: 1) inpatient and residential care, 2) intensive outpatient and partial hospitalization treatment, and 3) outpatient. Illustrative case studies also are presented to highlight distinctions between levels of care and athlete-specific nuances to treatment approaches and health care teams. Finally, we review aspects of return to play plans for elite athletes with EDs.